Creativity and psychopathology: the tenacious mad-genius controversy updated. (June 2019) - Simonton, Dean Keith
Highlights: Although the creativity psychopathology question is centuries old, it still lacks a scientifically satisfactory answer. Successful resolution of this problem likely requires that researchers more carefully attend to seven problematic issues. These issues concern target persons, mental disorders, creative domains, hypotheses, assessments, analyses, and explanations. Taken together, these issues demonstrate that the mad-genius debate cannot possibly have a simple answer. Abstract : The mad-genius controversy concerning the relation between creativity and psychopathology is one of the oldest and most contentious in the behavioral sciences. Although the prevailing consensus is that the debate is not specious, it is also evident that its scientific resolution is far more complicated than a mere yes–no decision. To illustrate this complexity, this article examines seven central issues that must be addressed in future research: target persons, mental disorders, creative domains, specific hypotheses, quantitative assessments, data analyses, and theoretical explanations. It thus becomes apparent that the subject should continue to attract empirical and theoretical work well into the future.